Asymmetric cell division: microtubule dynamics and spindle asymmetry. - Kaltschmidt, J.A.; Brand, A.H. (Journal of Cell Science, 2002)
Asymmetric cell division can produce daughter cells with different developmental fates and is often accompanied by a difference in cell size. A number of recent genetic and in vivo imaging studies in Drosophila and Caenorhabditis elegans have begun to elucidate the mechanisms underlying the rearrangements of the cytoskeleton that result in eccentrically positioned cleavage planes. As a result, we are starting to gain an insight into the complex nature of the signals controlling cytoskeletal dynamics in the dividing cell. In this commentary we discuss recent findings on how the mitotic spindle is positioned and on cleavage site induction and place them in the context of cell size asymmetry in different model organisms.